2003
DOI: 10.1007/s00109-003-0491-2
|View full text |Cite
|
Sign up to set email alerts
|

Transduction efficiency of MLV but not of HIV-1 vectors is pseudotype dependent on human primary T lymphocytes

Abstract: The success of several gene therapeutic approaches requires efficient transduction of human primary T lymphocytes. For this it is important to enhance the transduction efficiency, and this can be achieved by various means, mainly technical development of transduction procedures and use of different vectors and vector pseudotypes. We analyzed the transduction efficiency of an HIV-1 vector encoding enhanced green fluorescent protein (GFP) as a marker gene and pseudotyped with the envelopes of MLV-A, MLV-10A1, Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…Lymphocytes were treated with either PHA plus IL-2 or with IL-7, which induce cell proliferation or G 0 /G 1b transition but induced only marginal cell proliferation under the conditions used here, respectively (4,11). Dividing PHA-IL-2-stimulated lymphocytes were susceptible to transduction with both retroviral vectors, although the percentage of F-MLV-transduced cells was lower than that of HIV-1-transduced cells, as reported by others (26). On the contrary, although IL-7-treated lymphocytes were susceptible to HIV-1 transduction, albeit with variations depending on the donor, they were largely resistant to F-MLV and were transduced at rates below 1% for a multiplicity of infection (MOI) of 25.…”
Section: Transduction Of Primary Gm-csf-derived Human Macrophages Andsupporting
confidence: 71%
“…Lymphocytes were treated with either PHA plus IL-2 or with IL-7, which induce cell proliferation or G 0 /G 1b transition but induced only marginal cell proliferation under the conditions used here, respectively (4,11). Dividing PHA-IL-2-stimulated lymphocytes were susceptible to transduction with both retroviral vectors, although the percentage of F-MLV-transduced cells was lower than that of HIV-1-transduced cells, as reported by others (26). On the contrary, although IL-7-treated lymphocytes were susceptible to HIV-1 transduction, albeit with variations depending on the donor, they were largely resistant to F-MLV and were transduced at rates below 1% for a multiplicity of infection (MOI) of 25.…”
Section: Transduction Of Primary Gm-csf-derived Human Macrophages Andsupporting
confidence: 71%
“…In addition, amphotropic MLV pseudotypes transduced cytokine-mobilized, human peripheral blood CD34+ cells capable of establishing hematopoiesis in immunodeficient mice more efficiently than VSV-G pseudotypes. Work reported by Muhlebach et al [Muhlebach, 2003] revealed that MLV vectors pseudotyped with the MLV 10A1 and the GALV GPs resulted in efficient transduction of preactivated human primary T lymphocytes while pseudotypes bearing the amphotropic MLV, RD114 and VSV-G GPs were less efficient. In contrast, HIV-1 vectors pseudotyped with the same GPs transduced preactivated T lymphocytes with similar efficiencies.…”
Section: Lentiviral Vectors Pseudotyped With Gammaretrovirus Gps Inmentioning
confidence: 98%
“…The high transduction efficiency of primary human T cells using the MLV-10A1 pseudotype is based on the usage of both Pit1 and Pit2 for cell entry Miller and Chen, 1996;Uckert et al, 1998). There are contrasting reports with regard to the transduction efficiency of human T cells achieved with the endogenous feline retrovirus RD114 pseudotype (Porter et al, 1996;Onodera et al, 1998;Uckert et al, 2000;Muhlebach et al, 2003;Strom et al, 2003). High transduction efficiencies obtained with the envelope of vesicular stomatitis virus G protein (VSV-G) are most probably due to the use of high multiplicities of infection (MOI).…”
Section: Selecting the Vector Envelopementioning
confidence: 95%
“…High transduction efficiencies obtained with the envelope of vesicular stomatitis virus G protein (VSV-G) are most probably due to the use of high multiplicities of infection (MOI). When VSV-G pseudotyped retrovirus vectors were carefully equilibrated in titer to other pseudotypes transduction efficiency dramatically decreased (Muhlebach et al, 2003). Primary murine T cells are most efficiently transduced by retroviral vectors carrying the ecotropic MLV envelope (Hagani et al, 1999;Engels et al, 2003).…”
Section: Selecting the Vector Envelopementioning
confidence: 99%